Palynofacies and predictions for hydrocarbon generation potential of the Upper Cretaceous lignite from Maiganga Coalfield, Northern Benue Trough, Nigeria. (Journal of Pure and Applied Sciences (Science Forum), 2025)
The Upper Cretaceous Coalfield of Northern Benue Trough, represent excellenthydrocarbon source rock potential within the Nigeria inland basins. The source rockpotential of coal and shale whole rock samples from Maiganga and Yaya-Ngari areas inthe Northern Benue Trough was investigated using palynofacies and organicgeochemical methods for hydrocarbon generation predictions. Palynofacies is integratedin this study as a useful tool for kerogen typing, paleoenvironment indicator, thermalmaturity determination and hydrocarbon generation potential of source rock whichequally relies on the relative abundance of the three kerogen groups (AMO, Phytoclastand palynomorphs). Current result shows that identified palynomorphs (P), phytoclast(Ph) and amorphous organic matter (AOM) for the studied Yaya-Ngari shale showsignificant amount of dark-brown to orange colour phytoclast compared to brownheterogenous AOM and brown to orange palynomorphs. The palynomorphs are often